2019
DOI: 10.1111/mcn.12887
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and determinants of gestational weight gain among pregnant women in Niger

Abstract: Low gestational weight gain (GWG) and low mid-upper arm circumference (MUAC) are associated with adverse pregnancy outcomes. We aimed to assess the prevalence and determinants of low GWG and low MUAC among pregnant women in rural Zinder, Niger. A community-based survey was conducted among 1,384 pregnant women in the catchment areas of 18 integrated health centers in the region of Zinder, Niger. Weight and MUAC were measured during an in-home visit and again 1 month later, when haemoglobin concentration and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 51 publications
2
14
0
Order By: Relevance
“…Table 1 describes the characteristics of the studies included in this review. Five studies were from Nigeria [6,7,[42][43][44]; four from Cameroon [45][46][47][48]; four each from Ethiopia [2,35,49,50] and Ghana [39,[51][52][53]; two studies from South Africa [54,55] and Malawi [28,56]; and one each from Uganda [9], Kenya [57], Niger [58], Benin [40], and the Democratic Republic of Congo [59]. Based on a country's income status [60], two studies were from upper middleincome countries [54,55]; fourteen from lower middle-income countries [6, 7, 39, 42-48, 51-53, 57] and ten from low-income countries [2,9,28,35,40,49,50,56,58,59].…”
Section: Results Of the Screening Processmentioning
confidence: 99%
See 4 more Smart Citations
“…Table 1 describes the characteristics of the studies included in this review. Five studies were from Nigeria [6,7,[42][43][44]; four from Cameroon [45][46][47][48]; four each from Ethiopia [2,35,49,50] and Ghana [39,[51][52][53]; two studies from South Africa [54,55] and Malawi [28,56]; and one each from Uganda [9], Kenya [57], Niger [58], Benin [40], and the Democratic Republic of Congo [59]. Based on a country's income status [60], two studies were from upper middleincome countries [54,55]; fourteen from lower middle-income countries [6, 7, 39, 42-48, 51-53, 57] and ten from low-income countries [2,9,28,35,40,49,50,56,58,59].…”
Section: Results Of the Screening Processmentioning
confidence: 99%
“…Sixteen studies [2, 7, 9, 28, 35, 42, 45, 47, 51-56, 58, 59] classified the outcome (GWG) according to the IOM recommendations, but for seven studies [6,39,40,43,44,48,50] standard criteria were not used to measure and classify the outcome, that is the authors classified weight gain using their own method. Three studies reported according to the International Fetal Newborn Growth Standards for the 21st Century (INTERGROWTH-21 st ) guidelines [52,57,58], of which two studies [52,58] used both IOM 2009 and INTERGROWTH-21 st guidelines. The authors of one study stated that they used the IOM classification, but they also reported normal weight gain as "women with BMIs between 18.5 kg/m 2 and 30 kg/m 2 and who gained 9 to 16 kg; excessive weight gain for those who gained weight above these ranges" [46].…”
Section: Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations